Health Informatics : Selected Papers from the 19th Australian National Health Informatics Conference (HIC 2011) - Hansen, D. P.; Maeder, A. J.; Schaper, Louise K. (Studies in health technology and informatics, 2011)
Australia has a long history of involvement in the progress of health informatics, and Australian contributors have made an impact on the world health informatics scene in numerous areas, including software development, standardization, evaluation, policy development and education. The Health Informatics Society of Australia (HISA), has been reporting on these developments for 19 years, and its annual Health Informatics Conference (HIC) constitutes the premier Australian academic platform for a wide range of topics in health informatics. This book presents the proceedings of full scientific pa.